Evaluation of palm oil mill effluent (POME) by membrane anaerobic system (MAS) - Rajaletchumy, Veloo Kutty (2010)
The evaluation of anaerobic digestion process of palm oil mill effluent (POME) was carried out in a laboratory-scale membrane anaerobic system (MAS). The MAS consists of a cross-flow Ultra-filtration membrane for solid-liquid separation and operational pressure of 1.5 to 2 bars. An enrichment mixed culture of methanogenic bacteria was developed and acclimatized in the digester for three days when the POME is fed into the 30 L digester combining Ultrafiltration (UF) membrane MAS is a modern bioreactor and was used for the rapid biotransformation of organic matter to Methane gas with the help of Methanogenic bacteria. Two concentration ratios of 50% and 100% of the raw POME were studied. The hydraulic retention time (HRT) ranged between 1 and 4 days. Throughout the experiment, the removal efficiency of COD was between 78.81% and 81.44%. The methane gas production rate was 0.673 L/g COD/d to 0.974 L/g COD/d. The effluent flow rates for the two ratios were found as 10.31 L/d and 21.75 L/d respectively. The pH was between 6.8 and 7.7. The membrane anaerobic system, MAS treatment efficiency was greatly affected by solid retention time, hydraulic retention time and organic loading rates. In this study, membrane fouling and polarization at the membrane surface played a significant role in the formation of the strongly attached cake layer limiting membrane permeability.